Online guided reflection sessions: getting learners to think about the process of learning - Laura Hamilton (Journal of Learning Development in Higher Education)
This 20-minute presentation showcased a series of ‘guided reflection’ sessions which have been used to support the social, emotional, and academic development of foundation year students at the University of Surrey. This group of students arrive at university having not obtained the necessary grades for direct entry onto the first-year undergraduate programme and they report difficult relationships with study and often have fixed beliefs and academic behaviours. This may impact their progression if learners hang on to previously unsuccessful academic behaviours which are also, sadly, likely to reinforce their beliefs about their own academic potential.